Caracterização bioquímica das vesículas extracelulares isoladas das cepas Y e Yuyu do Trypanosoma Cruzi - Ribeiro, Kleber Silva [UNIFESP] (2017)
Abstract The Trypanosoma cruzi, the etiologic agent of Chagas disease, releases EVs containing a wide range of surface glycoconjugates of the parasite. Extracellular vesicles (EVs) are particles released by different cell types and pathogens, under physiological and pathological conditions, containing proteins, lipids and nucleic acids. In the present work, we purified, isolated and compared EVs from Y strain (DTU Tc II) and YuYu strain (DTU Tc I) of T.cruzi, that belonging to different discrete typing units (DTU) and having a different degree of virulence. Initially, scanning electron microscopy (SEM) was performed to visualize the trypomastigote form of T.cruzi releasing the EVs from the plasma membrane and visually the trypomastigotes of the YuYu strain released more particles. The characterization of EVs about size and concentration was done using the nanoparticle tracking analysis (NTA) technology. Don't had significant difference when compared the mean size (150nm) of the EVs, but the concentration of particles in the YuYu strain sample was higher than in the Y strain sample, confirming the SEM analysis. Qualitative analysis by immunoblotting showed that EVs from both strains express transialidase (TS) and cruzipain, but the expression is higher in EVs from YuYu strain. By LC-MS/MS, the major glycoconjugates belonging to T. cruzi multigenic families, such as TS, Mucins, mucin-associated surface proteins (MASP), GP63 surface proteins, among others, were detected in EVs of both strains, but it was possible to identify more different proteins in EVs from YuYu strain than in EVs from Y strain. Phospholipid (PL) analysis by Thin Layer Chromatography (TLC), GC-MS and MALDI-TOF suggests the presence in EVs of PL such as phosphatidylcholine (PC), phosphatidylethanolamine (PE), phosphatidylinositol (PI) and phosphatidylserine (PS). The YuYu strain, which is more virulent, releases more EVs containing more proteins and expressing more of the glycoconjugates in common with EVs from Y strain. This difference may be important in parasite infectivity, since the EVs have a function of intercellular communication at distance and direct contact and may be involved in different mechanisms during parasite-host interaction such as cellular invasion, immunomodulation and evasion of the host immune system.